APLIKASI VITAMIN E DALAM PEMATANGAN GONAD INDUK GUPPY BLUE SKY (Poecilia reticulata) - Addurrohim , Muhammad Febian; Kusumanti, Ima; Iskandar, Andri; Ramadhani, Dian Eka; Rozak , Dedi Abdul (JARI : Jurnal Akuakultur Rawa Indonesia, 2025)
Guppy fish cultivation has become a promising business opportunity due to its high economic value and market demand. One of the challenges frequently faced by guppy fish breeders is the low larva production caused by inadequate nutrition intake in their feed. One important nutrient in the parent feed is vitamin E, which plays a crucial role in the fish reproduction process. This applied research aims to assess the effectiveness of administering vitamin E in the gonad maturation process of guppy fish. The study utilizes three treatments: control, P1 (4 mg/g), and P2 (6 mg/g), using the randomized block design with three replications. The research procedure includes preparing containers, test feed, and measuring research parameters. The observed research parameters include abnormalities, parental and offspring survival rates, absolute length growth of the parents, larval production, and water quality. The most optimal dose of vitamin E is indicated by P1 (4 mg/g), which resulted in a parental absolute length growth value of 0,57±0,06a cm and produced 278±7,55b larvae per parent. Survival rate of parents and seeds was found to be 100% with no deaths during research activities.